Analisis Kemampuan Komunikasi Matematis Lisan dan Tulisan Siswa dalam Menyelesaikan Soal - Zhabriani, Khalifa; Mubarik, Mubarik; Murdiana, I Nyoman; Hadjar, Ibnu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
21st century skills are termed the 4C which stands for Critical Thinking, Collaboration , Communication, and Creativity. The purpose of this research is to analyze and describe students' mathematical communication skills in solving SPLDV story problems. This type of research uses descriptive research with a qualitative approach to describe students' mathematical communication skills in solving SPLDV problems based on extroverted and introverted personality types. The subjects in this study were 2 students of class VIII of SMP Negeri 7 Palu in the academic year 2023/2024 consisting of one student each with extroverted personality type and one student with introverted personality type. The conclusion of this study shows that students with extroverted personalities tend to be more active in communicating mathematical ideas verbally, while introverted students focus more on systematic written communication. Both personality types have different ways of solving SPLDV problems, but are able to achieve good solutions according to their respective abilities. Keywords: Ability, Mathematical Communication, Story Problem, Personality Type